Triploidy in Citrus Genotypes Improves Leaf Gas Exchange and Antioxidant Recovery From Water Deficit - Lourkisti, Radia; Froelicher, Yann; Herbette, Stéphane; Morillon, Raphael; Giannettini, Jean; Berti, Liliane; Santini, Jérémie (Frontiers in Plant Science, 2021)
The triploidy has proved to be a powerful approach breeding programs, especially in Citrus since seedlessness is one of the main consumer expectations. Citrus plants face numerous abiotic stresses including water deficit, which negatively impact growth and crop yield. In this study, we evaluated the physiological and biochemical responses to water deficit and recovery capacity of new triploid hybrids, in comparison with diploid hybrids, their parents (‘Fortune’ mandarin and ‘Ellendale’ tangor) and one clementine tree used as reference. The water deficit significantly decreased the relative water content (RWC) and leaf gas exchange (Pnet and gs) and it increased the levels of oxidative markers (H2O2 and MDA) and antioxidants. Compared to diploid varieties, triploid hybrids limited water loss by osmotic adjustment as reflected by higher RWC, intrinsic water use efficiency (iWUE Pnet/gs) iWUE and leaf proline levels. These had been associated with an effective thermal dissipation of excess energy (NPQ) and lower oxidative damage. Our results showed that triploidy in Citrus enhances the recovery capacity after a water deficit in comparison with diploids due to better carboxylation efficiency, restored water-related parameters and efficient antioxidant system.